Workshop report: The 2012 Antimicrobial Agents in Veterinary Medicine: exploring the consequences of antimicrobial drug use: a 3‐D approach1. Issue 1 (6th January 2014) - Martinez, M.; Blondeau, J.; Cerniglia, C. E.; Fink‐Gremmels, J.; Guenther, S.; Hunter, R. P.; Li, X.‐Z.; Papich, M.; Silley, P.; Soback, S.; Toutain, P.‐L.; Zhang, Q.
<x xml:space="preserve">Abstract</x> Antimicrobial resistance is a global challenge that impacts both human and veterinary health care. The resilience of microbes is reflected in their ability to adapt and survive in spite of our best efforts to constrain their infectious capabilities. As science advances, many of the mechanisms for microbial survival and resistance element transfer have been identified. During the 2012 meeting of Antimicrobial Agents in Veterinary Medicine (AAVM), experts provided insights on such issues as use vs. resistance, the available tools for supporting appropriate drug use, the importance of meeting the therapeutic needs within the domestic animal health care, and the requirements associated with food safety and food security. This report aims to provide a summary of the presentations and discussions occurring during the 2012 AAVM with the goal of stimulating future discussions and enhancing the opportunity to establish creative and sustainable solutions that will guarantee the availability of an effective therapeutic arsenal for veterinary species.